Dielectric Relaxation Studies of EMA,MMA&BMA with 2-Acrylamido 2- Methyl Propane Sulphonic Acid(AMPS)Copolymers (International Journal of Innovative Research in Engineering & Management, 2021)
Dielectric properties of EMA,MMA&BMA  with AMPS in composition (50/50) have been studied over  frequency range from 100Hz to 100kHz and temperature range  from room temperature to 180oC.The Copolymers characterized  by DSC. The frequency dependence of the dielectric constant  and dielectric loss has been investigated. Dielectric constant  decreases with increasing frequency and increases with  temperature. AC Conductivity calculated and data were  analyzed. The AC Conductivity increases with increasing  temperature and frequency. The present report deals with a  systematic study of dielectric property of EMA,MMA&BMA  with AMPS as a function of both frequency and temperature.
Keywords: Dielectricconstant(ε); Dielectricloss(tanδ); ACconductivity; Relaxation; segmental motion